STRATEGI KOMUNIKASI PEMASARAN VAPE STORE J VAPE GRAHA FAMILY SURABAYA - kurniawan, efreldo kris (The Commercium, 2023)
The problem to be investigated in this thesis is how the marketing communication strategy implemented by J'Vape Graha Family attracts consumer interest. In this research a qualitative descriptive method was used which explored facts about the Marketing Communication Strategy used by J'Vape Graha Family and then analyzed using marketing communication theory which used a deeper theory, namely the marketing communication mix. From the results of research on communication strategy marketing strategy used by J'Vape Graha Family, it can be found that the strategy undertaken by J'Vape Graha Family to market and introduce its products is1) J'Vape Graha Family uses advertisements on social media and non-social media,2) J'Vape Graha Family organizes member and telegram groups to do direct marketing3) J'Vape Graha Family provides discounts and giveaways to create sales promotions4) J'Vape Graha Family uses social media Instagram and Facebook to market its products with the Knownledge concept. Based on the findings, several suggestions can be taken into consideration for improving the quality of the marketing communication strategy used by J'Vape Graha Family, namely:1) maximize their social media because social media is the biggest impact on increasing sales of J'Vape Graha Family2) providing new innovations in social media, so it doesn't always make story telling but instead makes the Instagram feed more attractive from a visual standpoint3) not focusing on social media because other strategies if maximized will also have an impact on increasing sales for J'Vape Graha Family